(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2018)
Manzoni’s library is now coming under a new exhaustive inventory of the marginalia that can be found inside it. The different kind of marginal notes will be available soon on the new portal Manzoni online which will offer many important opportunities of research. My own essay inquires into a little known side of marginalia (so-called dog-ears) wich is quite hard to investigate and attempts to explain how Manzoni studied and recorded his linguistic references.